Observation of The Natural PH of Some Flower and Plant Samples on The Campus Universitas Wijaya Kusuma Surabaya - Kapuka, Gius; Firdaus, Solichatul; Anisa, Siti (Journal of Natural Sciences and Learning, 2024)
The purpose of this study was to observe the acid-base pH of several samples of flowers and plants around the campus. To recognize acids and bases is usually by using indicators. The purpose of acid-base indicator analysis is to measure acid-base reactions. This usually requires the use of indicators or tools such as litmus paper, pH indicator paper, and electrodes for acids and bases. Indicators were extracted from Allamanda flower plants, Bougainvillea flowers, and Dracaena reflexa plants using solvents (water) and alcohol. The method used in this study is the practicum method and literature review using Google Scholar articles and sources.